Preparation of activated carbon from palm oil wastes and their application for methylene blue removal (2017)
The production of activated carbon from residual biomass generated in the production of oil palm, fiber (F) and shell (C) was studied. The chemical activation was done using ZnCl2 and the adsorption capacity of methylene blue (AM) at different concentrations (50, 100, and 150 mg/L) was evaluated. Results showed a good development of pore with surface areas of 835.3 m2/g for activated fiber (FA) and 575.1 m2/g for activated shell (CA). A good fit of the experimental data with the pseudo second order kinetic model and with Langmuir and Freundlich isotherms models was found. In addition, maximum adsorption capacities of 763.4 and 724.6 mg/g for FA and CA were found, respectively. © 2017, Universidad Nacional de Colombia. All rights reserved.